Using Arts-Based Therapies to Improve Mental Health for Children and Young People With Physical Health Long-Term Conditions: A Systematic Review of Effectiveness - Wigham, Sarah; Watts, Patricia; Zubala, Ania; Jandial, Sharmila; Bourne, Jane; Hackett, Simon (Frontiers in Psychology, 2020)
Background. Children with physical health long-term conditions have increased risk of mental health difficulties relative to healthy peers. Evidence for best ways to provide psychological support for these children is limited. Methods. We conducted a systematic review of arts based therapies interventions for mental health in children with long-term physical health conditions. Electronic databases searched included the Cochrane library, Medline, Embase and PsycINFO and a narrative synthesis of the findings is presented. Results. Sixteen studies met inclusion criteria and demonstrated some improvements on standardised indicators of mental health and well-being including quality of life, coping behaviours, anxiety, self-concept and mood. Sources of potential bias in studies reviewed included limited details on intervention components, a lack of methods to ensure consistent intervention implementation, or assessment of feasibility for health service integration. Conclusions. The findings suggest arts based therapies may have some potential as a psychological support for children with physical health long-term conditions. Design limitations were identified however and are important to address in future studies to build a more robust evidence-base. Recommendations are made.